A simple analysis of polarization reversal of ferroelectric capacitor demonstrating negative capacitance-like behavior. (4th December 2019) - Tokumitsu, Eisuke
Abstract: Polarization reversal of a ferroelectric capacitor with a load resistance has been calculated by the Kolmogorov–Avrami–Ishibashi (KAI) model. Polarization change, current response and voltage across the ferroelectric capacitor were calculated and then the total charge density was plotted as a function of voltage across the ferroelectric capacitor to reconstruct polarization-electric field relation. Negative capacitance-like behavior was observed due to the voltage drop across the load resistance caused by the switching current of ferroelectric polarization reversal. In addition, circuit and switching parameter dependences on the negative capacitance-like behavior are discussed. It is shown that a dimensionality factor in the KAI model formulation affects the negative capacitance-like behavior. The presented calculation results indicate that the switching current during the polarization reversal is important to observe the negative capacitance-like behavior in the pulse response of the RC circuit with a ferroelectric capacitor, which is essentially different from the originally proposed concept of negative capacitance.